Application of Urea Based Selective Non-Catalytic Reduction of Nitric Oxide in the Combustion Effluent Containing Low Concentration of NOx. - Hossain, K. A.; Jaafar, M. N. M.; Mustafa, A.; Ani, F. N. (2004)
Selective Non-Catalytic Reduction (SNCR) of Nitric Oxide has been studied experimentally using commercial grade of urea in a pilot-scale diesel fired tunnel furnace. The furnace simulated small-scale combustion systems such as low capacity boiler, hot water heater, oil heater etc., where the operating temperature is in the range of about 900 to 1300 K. The experiment was conducted with low ppm of base line NOx ranged from 65 to 74 ppm. A significant amount of NOx reduction was achieved which was not pronounced by the previous researchers with urea SNCR for this low ppm of NOx. At a normalized stoichiometric ratio (NSR) of 4, a maximum of 54% reduction was achieved at 1128 K without adding any additives. The effective temperature window for the reaction was about 973 to 1183 K which was lower than that obtained by the previous researchers. Although the NOx reduction was improved and effective temperature window widened for higher injection rate of the reagent, the optimum temperature of reduction remained almost unaffected.